TECHNOLOGY AND CONSTRUCTIVE MODIFICATION OF FILTERING LAYER BASED ON HEAT-RESISTANT BASALT FIBER - Umirzakov Zukhriddin Akhtamjonovich (Western European Studies, 2026)
This paper presents a design-oriented and technology-focused analysis of forming a heat-resistant basalt fiber–based filtering layer for high-temperature, abrasive cement dust–gas flows. Building on global industrial experience and theoretical reasoning (without reporting experimental measurements), the study frames filtration performance as an integrated material–structure–regeneration system. A gradient (multi-layer) filtering architecture is substantiated, typically composed of a prefilter layer, a main basalt-fiber filtering layer, and a support/protection layer. The approach targets stabilization of pressure-drop growth and improved pulse-jet cleanability by controlling dust cake formation. Needle-punched basalt nonwoven structures are justified as a mechanically robust option under repeated pulse-jet loading, while optional hydrophobic and antistatic surface treatments are discussed as measures to reduce moisture-related cementation and electrostatic adhesion, thereby improving cake release. The main outcome is a calculation-based technological platform that links key filtration objectives (efficiency, pressure stability, cleanability, and durability) to controllable structural parameters of basalt-fiber media and provides a solid basis for subsequent laboratory and industrial validation
Keywords: basalt fiber; heat-resistant filtration media; cement dust